THE ROLE OF GREEN BUILDINGS IN SUSTAINABLE PRODUCTION: EXAMPLE OF INCI AKU INDUSTRIAL BATTERY FACTORY, TURKEY - Ferhat ARSLAN (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2017)
Abstract The excessive consumption of natural resources has required a reinterpretation of traditional development approaches. Thus, the term sustainability was suggested in the late 1980s as a key to change in production, as in many other areas and it ultimately leads to the eco-friendly manufacturing model called sustainable production. Today, the understanding of sustainability is becoming widespread, not only in the manufacturing sector but also in building construction. Green building applications are the reflection of the idea of sustainability in the construction sector and their aim is to transform structures into eco-friendly buildings using various grading systems. This paper’s goal is to discuss the dilemma between environmental protection and development and to point out the role of green buildings in sustainable production. The perspectives of industrialists on environmental sensitivity were investigated based on the interviews conducted by the authorities of an industrial battery firm, INCI, which has the first facility with a green building certificate in Turkey. This paper’s conclusions are: (1) Construction of green buildings can be effective in sustainable production. (2) Investments on environment protection can increase the interest rates of firms and (3) Sustainable production can be a solution for the environment-development dilemma.